A stainless steel easy-to-weld high-strength steel composite blank, composite material and preparation method
Through the electroslag welding composite method, microalloy stainless steel is combined with easy-to-weld high-strength steel billets to form composite bills and make composite materials through heating and rolling, which solves the problems of low interface bonding strength and high production cost of existing composite plates, and realizes the production of high-performance composite materials.
Patent Information
- Application Number
- CN202310893826.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-07-20
AI Technical Summary
During the production process, existing stainless steel/carbon steel composite panels have problems such as low interface bonding strength, high production cost and poor composite performance.
The electroslag welding composite method is used to form a blank by covering the microalloy stainless steel with easy-to-weld high-strength steel with alkaline slag to form a microalloy stainless steel easily welded high-strength steel composite blank, and a composite material is made by heating and rolling.
The strength, toughness, plasticity, local corrosion resistance and seawater corrosion resistance of composite materials are improved, while reducing production costs, and the interface bonding strength can reach 220-600MPa and above.
Smart Images

Figure CN117102657B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal materials, and in particular to a stainless steel easy-to-weld high-strength steel composite blank, a composite material and a preparation method thereof. Background Art
[0002] Metal composite materials refer to composite materials formed by metallurgical bonding at the interface using composite technology or multiple metals with different chemical and mechanical properties. They greatly improve the thermal expansion, strength, fracture toughness, impact toughness, wear resistance, electrical properties, magnetic properties and many other properties of single metal materials. Therefore, they are widely used in industrial fields such as petroleum, chemical industry, marine engineering, shipbuilding, metallurgy, mining, machinery manufacturing, electricity, water conservancy, transportation, environmental protection, pressure vessel manufacturing, food, brewing, and pharmaceuticals.
[0003] Metal composite material technology can give full play to the advantages of each component material, achieve the optimal configuration of each component material resource, save precious metal materials, and achieve performance requirements that cannot be met by a single metal. Taking stainless steel / carbon steel composite plates for pressure vessels as an example, the base layer uses general carbon steel (Q245R, Q345R, etc.) with good mechanical properties, and the cladding layer uses stainless steel (304, 316L, etc.) with good corrosion resistance. The two are usually explosively welded together, requiring only a few millimeters of expensive stainless steel, saving a lot of costs, and almost not changing the various mechanical properties of the substrate. It can not only replace imports and fill domestic gaps, but also has a wide range of applications, with good economic and social benefits.
[0004] Iron-based composite materials introduce steel, a cheap and abundant raw material, and can be promoted on a large scale. For example, structural parts such as engine parts that operate under high temperature, high speed and wear resistance conditions can fully meet their working needs, and their cost performance is higher than that of aluminum-based, magnesium-based and other composite materials. Therefore, considering the economic cost and actual application effect, iron-based composite materials have broad application prospects due to their high cost performance.
[0005] At present, the main production methods of composite plates are explosion method, rolling method, explosion + rolling composite method and double roll casting method. Although the explosion method can realize the composite of any metal parts, it has obvious shortcomings such as pollution during the explosion and difficulty in preparing thin composite plates. The rolling method is easy to form and convenient for batch production, but because the composite interface cannot produce atomic bonding, the interface bonding force of the composite layer is low. The explosion + rolling composite method combines the advantages of the above two methods, and thus has the advantages of high production efficiency, mature technology, and easy continuous large-scale production. It has become the main production method of stainless steel / carbon steel composite plates [Li Xingbo. Research on thermal deformation behavior of bimetallic composite plates [D]. Qinhuangdao: Yanshan University, 2016: 12.]. By optimizing the composition of the stainless steel substrate material (such as Ni, N, La and Ti, etc.) and process optimization (rolling reduction rate, rolling temperature, heat treatment, etc.) [Liu Huiyun, He Yi, He Bingleng, et al. Effect of heat treatment on the microstructure and properties of hot-rolled microalloyed stainless steel composite plate [J]. Journal of Materials Heat Treatment, 2016, 37(7): 106110.], the interface bonding strength can be improved, but there are also great limitations [Wang K, Yu H, Tian Y, et al. Tailoring of interface microstructure and Laondingproperty in 1Cr17 / 8Cr13MoV / 1Cr17 stainless steel clad plate with Niinterlayer [J]. Materials Science and Engineering: A, 2022, 838: 142778.]. The twin-roll casting method is a newly developed material composite technology, which is more suitable for the composite of low-melting light metal and steel materials [Xu Tao. Development and Application of Metal Layered Composite Materials [J]. Light Alloy Processing Technology, 2012, 40 (6): 710.]. Michele et al. successfully prepared stainless steel / carbon steel composite plates by twin-roll thin strip continuous casting, with good interface bonding and an average shear strength of only 218 MPa [Vidoni M, Ackermann R, Richter S, et al. Production of clad steel strips Laytwin-roll strip casting [J]. Advanced Engineering Materials, 2015, 17 (11): 15881597.], and the interface bonding strength is low. In view of this, the present invention provides a stainless steel easy-to-weld high-strength steel composite blank, a composite material and a preparation method. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a stainless steel easy-to-weld high-strength steel composite blank, a composite material and a preparation method. The purpose is to provide a composite blank with a simple process, which has the excellent mechanical and corrosion resistance of microalloyed stainless steel (including microalloyed low-cost martensitic stainless steel, microalloyed low-cost ferritic stainless steel or microalloyed nickel-saving austenitic stainless steel), and the toughness and weldability of easy-to-weld high-strength steel, thereby reducing the production cost and improving the strength, toughness, plasticity, local corrosion resistance and seawater corrosion resistance of the composite material obtained by hot rolling the composite blank.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a stainless steel easy-to-weld high-strength steel composite billet, comprising the following steps: using easy-to-weld high-strength steel as a master batch, using microalloyed stainless steel as a consumable electrode, and using alkaline slag as a covering agent, performing electroslag welding, wherein the voltage of the electroslag welding is 30-45V, the current is 1000-2000A, and the time is 0.5-3.5 hours, and cooling to obtain the microalloyed stainless steel easy-to-weld high-strength steel composite billet.
[0008] The above-mentioned electroslag welding (also known as electroslag casting) refers to an electroslag metallurgical process that completes metal refining and casting at one time to produce high-quality alloy castings. It uses the resistance heat generated by the current passing through the liquid slag to continuously melt the metal electrode, and the molten metal gathers into droplets, drips through the slag layer into the metal molten pool, and solidifies into a casting in a special-shaped water-cooled mold. The above-mentioned fusion welding cooling is water cooling or air cooling.
[0009] The existing solid-solid hot rolling composite method mainly applies a certain amount of energy to the bonding interface by heating and mechanical methods to achieve the metallurgical bonding between the bimetals. The present invention is different from it in that it adopts a liquid-solid composite method, which mainly achieves the metallurgical bonding between the bimetals through the direct action of liquid and solid at high temperature. This is more conducive to the diffusion of various components and the improvement of interface bonding strength, and is also more conducive to the preparation of composite materials with different structures and performance requirements.
[0010] The electroslag welding composite method adopted in the present invention is to composite materials with functions such as corrosion resistance and heat resistance (microalloyed low-cost martensitic stainless steel, microalloyed low-cost ferritic stainless steel or microalloyed nickel-saving austenitic stainless steel) onto structural materials with rigidity and toughness (easy-to-weld high-strength steel) to obtain microalloyed stainless steel easy-to-weld high-strength steel composite blanks, which are then heated and rolled to manufacture composite steel plates of various specifications (thickness, width, length) and the like.
[0011] The beneficial effects of the present invention are:
[0012] (1) The interface bonding strength of the microalloyed stainless steel easy-to-weld high-strength steel composite blank of the present invention can reach 220-600MPa or above;
[0013] (2) The present invention adopts the electroslag welding composite method, using microalloyed stainless steel as the cladding metal, which is combined with the easily welded high-strength steel to form a parent metal under the protection of pre-melted alkaline slag, effectively preventing oxidation;
[0014] (3) The present invention uses ingots of microalloyed stainless steel (microalloyed low-cost martensitic stainless steel, microalloyed low-cost ferritic stainless steel or microalloyed nickel-saving austenitic stainless steel) instead of finished plates as raw materials, which greatly reduces costs.
[0015] Based on the above technical solution, the present invention can also be improved as follows.
[0016] Furthermore, the easy-to-weld high-strength steel comprises the following chemical components by mass percentage: C: 0.009-0.049%, Si: 0.011-0.049%, Mn: 0.51-1.49%, 90×10 -4 %≤Mg+Zr≤130×10 -4 %, and the content of Mg and Zr satisfies Zr / Mg=3~6, and the balance is Fe.
[0017] The above further beneficial effects of the present invention are as follows: the high-strength steel of the present invention adopts easy-to-weld high-strength steel. The composite microalloying of Zr and Mg is mainly used to refine the grains and improve the strength. The composite deoxidation and microalloying of Zr and Mg are mainly used to form fine, dispersed and spherical non-metallic inclusions. After the composite deoxidation treatment, the size of the inclusions in the high-strength steel is significantly refined, mainly concentrated in 1-3μm, which can significantly improve the plasticity and toughness of the matrix steel. The low-carbon chemical composition design is mainly used to improve the weldability of the steel plate. The advantages of composite deoxidation of Zr and Mg are mainly reflected in: the fine, dispersed and spherical non-metallic inclusion particles can promote the nucleation of needle-shaped ferrite, thereby refining the grains and improving the strength, plasticity, toughness and weldability of the steel. First, the composite deoxidation of Zr and Mg can enhance the deoxidation capacity; second, ZrO2 is a vacancy oxide, which interacts with the solute atom Mn in the steel, promotes the formation of Mn solute poor area and promotes the nucleation of ferrite; third, the crystallography of ZrO2 and MnS is highly similar, which is conducive to the precipitation of MnS on the oxide, promotes the formation of Mn solute poor area and ferrite nucleation, and can reduce the adverse effect of MnS inclusions on plasticity and toughness. In addition, since the density of ZrO2 is close to that of molten steel, it has low interfacial energy, contact angle and conductivity. During the refining process of molten steel, ZrO2 particles repel each other, are not easy to aggregate and grow, and are easy to be evenly and dispersedly distributed. Furthermore, the oxides formed by Zr and Mg are high-temperature stable oxides, which play a good role in pinning austenite grain boundaries and grain refinement during hot working and welding thermal cycles.
[0018] The roles of the above components in easy-to-weld high-strength steel are as follows:
[0019] C: Carbon is the most important element in steel and also one of the cheapest elements. Carbon is a strong interstitial solid solution element. Adding carbon to steel can have a significant interstitial solid solution strengthening effect on steel, thereby improving the strength of low-alloy high-strength steel, and it contributes the most to the strength of steel. Carbon combines with microalloy elements (Zr, Ti, V, etc.) in steel to form carbides, especially forming fine, dispersed carbide inclusions in austenite, which plays a role in grain refinement and precipitation strengthening, and improves the hardness and strength of steel. When the carbon content in steel increases, the yield and tensile strengths increase, but the plasticity and impact toughness will decrease, and its welding performance will also be impaired. In order to adapt to high heat input welding and improve the toughness of steel, the carbon content of low-alloy high-strength steel can be appropriately reduced, which can improve the low-temperature impact toughness and welding performance of the steel plate. The carbon content of low-alloy structural steel used for welding is generally not more than 0.20%. The steel of the present invention adopts an ultra-low carbon design, and the carbon content is reduced to below 0.05%, which can effectively improve the toughness of the heat-affected zone of large-line energy welding and reduce the welding crack sensitivity of steel. The use of low-carbon design in low-alloy high-strength steel will inevitably cause strength loss. In order to ensure that high heat input welding steel still has high strength under the premise of low carbon, the present invention adopts composite microalloying treatment to improve strength by adding microalloying elements Zr and Ti.
[0020] Mn: Manganese is a weak carbide-forming element. Except for a small amount that is soluble in carburizer, it is almost soluble in austenite and austenite. It improves the hardness and strength of austenite and austenite in steel. Usually, the manganese content is increased to make up for the partial strength loss caused by reducing the carbon content. Manganese can significantly reduce the transformation temperature, strongly reduce the starting transformation temperature of grain boundary austenite, and promote the formation of acicular austenite. Manganese is also a good deoxidizer and desulfurizer. It is often added together with silicon and titanium for composite deoxidation to form composite inclusions with high sulfur capacity, which effectively induces the nucleation of acicular austenite in the crystal. Manganese and sulfur form MnS with a higher melting point, which can prevent the formation of FeS and produce hot brittleness. In addition, manganese has the tendency to increase the coarsening of steel grains, the sensitivity to temper brittleness and the sensitivity to overheating.
[0021] Si: Silicon can dissolve in austenite and austenite to increase the hardness and strength of steel, making up for some of the strength loss caused by reducing the carbon content. Silicon has a good deoxidizing effect in molten steel and is a good deoxidizer. When deoxidizing with aluminum, adding a certain amount of silicon can significantly improve the deoxidation ability of aluminum. However, too high a silicon content can promote the nucleation of grain boundary austenite, inhibit the formation of needle-shaped austenite, increase the content of MA components, reduce the plasticity and toughness of steel, and reduce the welding performance of steel. Therefore, the steel of the present invention adopts a low-siliconization design to inhibit the formation of MA and grain boundary austenite.
[0022] Zr: Zirconium is a commonly used deoxidizer, and due to the composite deoxidation with titanium or aluminum titanium, fine dispersed composite inclusions are formed. This composite inclusion pins the grain boundary movement during the welding thermal cycle to limit the growth of austenite grains, and induces needle-shaped austenite nucleation during the austenite transformation process, so that the grains are effectively refined and the toughness of the coarse-grained zone of the weld is improved. However, excessive zirconium will also cause coarse particles and lose the effect of inhibiting grain coarsening. Adding an appropriate amount of Zr (0.001-0.10wt%) to the steel of the present invention is conducive to the formation of fine inclusions, the formation of needle-shaped austenite, and the refinement of the structure, and improves strength, weldability, and corrosion resistance.
[0023] Mg: Magnesium is a strong deoxidizing element and a composite oxysulfide forming element. It can reduce the number of inclusions in steel, reduce their size, make their distribution uniform, and improve their morphology. Trace amounts of magnesium can improve the carbide size and distribution of microalloyed stainless steel. The carbide particles are small and uniform, and the MgO inclusions formed have the effect of pinning the austenite grain boundaries, which has a good control effect on the grain size.
[0024] In short, the easy-to-weld micro-alloy high-strength steel prepared above does not contain high-cost alloying elements such as Ni, Cu, Mo, Cr, and does not add rare earth and nitrogen elements that are difficult to smelt. It uses low-cost elements such as silicon and manganese to obtain good mechanical properties; at the same time, zirconium and magnesium elements are added in combination to improve welding performance while obtaining good corrosion resistance.
[0025] Furthermore, the easy-to-weld high-strength steel is prepared by the following steps: the chemical components of the easy-to-weld high-strength steel are first smelted in a vacuum induction furnace, then cast into a steel billet by a die casting process, and finally forged or hot-rolled. Alternatively, the chemical components of the easy-to-weld high-strength steel are first smelted in a converter or an electric furnace, then refined in an LF furnace, a VD furnace or an RH furnace, then cast into a steel billet by a continuous casting process, and finally forged or hot-rolled.
[0026] Furthermore, the microalloyed stainless steel includes microalloyed low-cost martensitic stainless steel, microalloyed low-cost ferritic stainless steel or microalloyed nickel-saving austenitic stainless steel.
[0027] Furthermore, the microalloyed low-cost martensitic stainless steel comprises the following chemical components by mass percentage: C: 0.26-0.29%, Si: 0.19-0.49%, Mn: 0.19-0.49%, S≤0.0015%, P≤0.015%, Ni: 1.1-1.9%, Cr: 12.1-13.9%, Ti: 0.0050-0.0060%, 90×10 -4 %≤Zr+Mg≤130×10 -4 %, and the contents of Zr and Mg satisfy Zr / Mg=2-4, with the remainder being Fe and unavoidable impurities;
[0028] The roles of the various elements in the above-mentioned medium-microalloyed low-cost martensitic stainless steel are as follows:
[0029] C: The content is generally controlled below 0.03%. Low carbon content not only ensures good strength and toughness of the material, but also greatly improves the weldability, cold working performance and corrosion resistance of the steel. However, as the carbon content decreases, the strength of the steel will decrease. In martensitic aging microalloyed stainless steel, elements such as Ti and Nb are added to make up for the strength of the steel. During the heat treatment process, a dispersion strengthening phase is formed. C and Cr can form stable carbides and precipitate at the grain boundaries to form Cr. 23 Carbides such as C6 not only reduce the effective Cr content in the steel matrix but also deteriorate the corrosion resistance of the material. Therefore, the mass content of C used in the present invention is 0.26-0.29%, which is beneficial to improve the corrosion resistance.
[0030] Cr: Cr plays a key role in the corrosion resistance of martensitic stainless steel. The Cr content of conventional martensitic stainless steel is generally 10.5%-18%. In the material's resistance to environmental corrosion, Cr can effectively improve the material's pitting potential, thereby reducing the sensitivity of pitting corrosion. Cr can form a dense Cr2O3 protective film on the surface of the steel, thereby achieving good corrosion resistance. During aging heat treatment, the combination of chromium and other alloying elements leads to a reduction in the effective Cr content of the matrix. The basic requirement to ensure the corrosion resistance of martensitic stainless steel is that it must contain a chromium content of 10.5%. At the same time, when the Cr content is too high, some ferrite will appear in the matrix after solution treatment, resulting in a reduction in the amount of martensite in the matrix. In the matrix, ferrite has a certain effect on the thermoplasticity of the material, causing the strength of the steel to decrease, the corrosion resistance to decrease, and the transverse toughness to decrease. In order to obtain good performance, the weight percentage of Cr added in the present invention is 12.1-13.9%.
[0031] Ni: The nickel content of conventional martensitic stainless steel is in the range of 6%-11%. Ni performs well in expanding the austenite phase and improving the stability of austenite. It is a typical element for forming austenite. Nickel will reduce the initial transformation temperature Ms of martensite, and its effect is stronger than that of chromium. In order to ensure that martensitic stainless steel is completely transformed into low-carbon lath martensite during the process of cooling from high temperature to room temperature during solution treatment, the nickel content in the material cannot be too high. Nickel is infinitely dissolved in the iron matrix, making it difficult for screw dislocations in the material to decompose, causing cross slip to occur, and reducing the interaction between dislocations and interstitial atoms. In order to make martensitic stainless steel have good toughness, Ni can form intermetallic compounds with elements such as Ti and Al during aging heat treatment. The precipitation strengthening effect of these intermetallic compounds is the key to improving the strength of high-strength martensitic stainless steel. Therefore, the mass content of Ni added in the present invention is 1.1-1.9%.
[0032] Mn: Mn has a smaller effect on expanding the austenite region. Its ability to stabilize the austenite phase is slightly lower than that of Ni. It has a good promoting effect on the hardenability of steel. The Mn content in martensitic stainless steel is generally ≤1%. Manganese can replace nickel in martensitic stainless steel, reduce the cost of martensitic stainless steel, and save nickel resources. It should be noted that this is only to replace nickel in the organization to obtain austenite, but it cannot replace nickel in terms of corrosion resistance. The addition of Mn will deteriorate the corrosion resistance of low Cr content microalloyed stainless steel. Manganese, as a deoxidizer in martensitic stainless steel, can form MnS with sulfur, inhibit the adverse effects of sulfur on the matrix, and improve the thermoplasticity of microalloyed stainless steel. Therefore, the mass content of Mn added in the present invention is 0.19-0.49%.
[0033] Si: Silicon is a strong delta ferrite stabilizing element that can increase the tempering brittleness temperature of martensitic stainless steel and inhibit the decomposition of residual austenite. Silicon can react with oxygen atoms in the surface layer of microalloyed stainless steel to form silicon-rich silicon oxides that cover the surface, thereby improving its resistance to high temperature and sulfuric acid corrosion. It can also improve the steel's oxidation resistance. - In a corrosive environment, Si can inhibit the further formation of pitting corrosion and has a good improvement effect on the pitting corrosion of martensitic aging microalloyed stainless steel. However, the amount of silicon added should not be too high, otherwise it will seriously affect the plasticity and corrosion resistance of the microalloyed stainless steel, and will also cause a decrease in weldability. Therefore, the mass content of the added Si is 0.19-0.49%.
[0034] S: Sulfur is regarded as a harmful impurity in austenitic stainless steel. The harmful effects of sulfur are mainly: reducing the thermoplasticity of austenitic stainless steel and affecting the hot workability of steel. This is due to the precipitation of MnS or (Fe, Mn)S along the grain boundaries at high temperatures; sulfur also reduces the corrosion resistance of austenitic stainless steel. MnS is easily soluble in acidic chloride solutions and often becomes a corrosion source, resulting in a significant reduction in pitting corrosion resistance and crevice corrosion resistance.
[0035] P: Phosphorus is generally regarded as a harmful impurity in austenitic stainless steel. The harmful effects of phosphorus are mainly: significantly reducing the corrosion resistance of chromium-nickel austenitic stainless steel in various concentrations of nitric acid in the solid solution state and sensitized state; significantly enhancing the corrosion resistance of chromium-nickel austenitic stainless steel in concentrated nitric acid and Cr-containing 5+ The sensitivity of solid solution intergranular corrosion in nitric acid reduces the corrosion resistance under these service conditions.
[0036] Zr: Zirconium is a strong carbide-forming element, a strong deoxidizing element and a complex oxysulfide-forming element. Adding a small amount of zirconium has the effects of degassing, purification and grain refinement, which is beneficial to improving the low-temperature performance of microalloyed stainless steel, improving the stamping performance, and significantly improving the hardenability of steel when dissolved in austenite. In austenitic steel, it can prevent intergranular corrosion of steel by oxidizing media. Due to the effects of fixed carbon and precipitation hardening, it can improve the high-temperature properties of heat-resistant steel, such as creep strength.
[0037] Mg: Its function is the same as described above.
[0038] In summary, the above-mentioned molten iron rich in chromium and nickel smelted from laterite nickel ore is used as the smelting raw material, and ultra-low P industrial pure iron and high carbon ferrochrome are used for batching, which saves the precious metal Ni. The low-cost martensitic stainless steel obtained does not contain high-cost alloying elements such as Mo and Nb, and obtains good mechanical properties by using low-cost silicon, manganese, chromium and other elements; at the same time, zirconium and magnesium elements are added in combination, so that good corrosion resistance is obtained while improving welding performance.
[0039] The microalloyed low-cost ferritic stainless steel comprises the following chemical components by mass percentage: C≤0.009%, Si: 0.19-0.49%, S≤0.0014%, P≤0.009%, Ni: 1.1-1.9%, Cr: 19.1-19.9%, Cu: 0.19-0.49%, N≤0.008%, 70×10 -4 %≤Mg+Zr≤290×10 -4 %, and the content of Zr and Mg satisfies Zr / Mg=3-6, and the balance is Fe and unavoidable impurities;
[0040] The roles of the above components in microalloyed ferritic stainless steel are as follows:
[0041] Cr: The higher the Cr content in ferritic stainless steel, the easier it is to passivate, making the surface of ferritic stainless steel less likely to be oxidized, thus having better corrosion resistance, and improving the ability to resist pitting corrosion, crevice corrosion and intergranular corrosion; at the same time, when the mass fraction of Cr is higher, the brittle phase in ferritic stainless steel will form faster. In addition, the speed of formation and precipitation of α' and σ phases is also related to the mass fraction of Cr. The higher the mass fraction of Cr, the faster the precipitation rate, and the precipitated phase will reduce the toughness of the steel and significantly increase the brittle transition temperature.
[0042] C, N: In addition to strengthening microalloyed stainless steel, C and N in ferritic stainless steel are almost harmful to other properties of microalloyed stainless steel, such as high brittle transition temperature, high notch sensitivity, and decreased corrosion resistance after welding, which are all related to C and N in steel. However, there is currently no way to completely avoid the presence of C and N in ferritic stainless steel. Since C and N are both elements that strongly form and stabilize austenite and expand the γ zone in Fe-Cr alloys, the important effect of C and N on the structure of ferritic stainless steel is to move the α+γ two-phase region toward a higher Cr content, so that ferritic stainless steel containing high C and N content may have a ferrite + martensite (austenite) two-phase structure. In addition, since the solubility of C and N in ferrite is very low, carbonitrides will precipitate during the subsequent cooling process after high-temperature heating, which has a very important effect on the properties of ferritic stainless steel.
[0043] Cu: It is a very weak austenite-forming element. The addition of a small amount generally does not have a significant effect on the organizational structure of ferritic stainless steel. Its main function is to improve the corrosion resistance and cold working formability of ferritic stainless steel.
[0044] Ni: Similar to C and N, it can also move the α+γ two-phase region of Fe-Cr alloy toward a higher Cr concentration. Ni can significantly improve the room temperature mechanical properties of ferritic stainless steel, especially the strength and toughness, and lower the brittle transition temperature of the steel. Adding Ni to ferritic stainless steel can further improve the steel's resistance to general corrosion, pitting corrosion and crevice corrosion in certain media, but it is harmful to the chloride stress corrosion resistance of ferritic stainless steel. In order to make Ni-containing ferritic stainless steel have a single pure ferrite structure, as the amount of Ni increases, it is necessary not only to increase the amount of Cr in the steel, but sometimes also to add ferrite forming elements such as Mo, Ti and Nb.
[0045] S: The function is the same as described above.
[0046] P: Function is the same as described above.
[0047] Zr: Zirconium is a stabilizing element with strong affinity to C and N. It is also a strong deoxidizing element and a composite oxysulfide forming element. Adding a small amount of zirconium has the effects of degassing, purification and grain refinement, which is beneficial to improving the low temperature performance of microalloyed stainless steel, improving the stamping performance, and significantly improving the hardenability of steel when dissolved in austenite. In austenitic steel, it can prevent intergranular corrosion of steel by oxidizing media. Due to the effects of fixed carbon and precipitation hardening, it can improve the high temperature properties of heat-resistant steel, such as creep strength.
[0048] Mg: Its function is the same as described above.
[0049] In summary, the above-mentioned use of molten iron rich in chromium and nickel smelted from laterite nickel ore as a smelting raw material saves precious metals Ni and Mo, and the obtained low-cost ferritic stainless steel does not contain high-cost alloying elements such as Nb, and uses low-cost silicon, copper, chromium and other elements to obtain good mechanical properties; at the same time, zirconium and magnesium elements are added in combination to improve welding performance while obtaining good corrosion resistance.
[0050] The microalloyed nickel-saving austenitic stainless steel comprises the following chemical components in terms of mass percentage: C: 0.09-0.14%, Si: 0.19-0.49%, Mn: 7.1-7.4%, S≤0.0014%, P≤0.014%, Ni: 1.1-1.9%, Cr: 17.1-17.9%, Cu: 0.49-0.99%, N: 0.26-0.34%, 90×10 -4 %≤Zr+Mg≤130×10 -4 %, and the content of Zr and Mg satisfies Zr / Mg=3-6, and the balance is Fe and inevitable impurities.
[0051] The roles of the above components in microalloyed nickel-saving austenitic stainless steel are as follows:
[0052] C: Carbon is an element that strongly stabilizes austenite and expands the austenite zone in austenitic stainless steel. Carbon interstitial atoms are dissolved in austenite, and the strength of austenite can be significantly improved through solid solution strengthening. However, carbon is often regarded as a harmful element in austenite. This is mainly because the presence of carbon reduces the electrode potential of iron and reduces corrosion resistance during some uses or processing. For example, heating or welding at 450-850℃ produces chromium depletion at the grain boundaries, which reduces the corrosion resistance of steel, especially the intergranular corrosion resistance. Carbon also increases the pitting tendency of chromium-nickel austenitic stainless steel, so the mass content of C in the above is 0.09-0.14%.
[0053] Si: Silicon is a strong ferrite-forming element. In austenitic stainless steel, as the silicon content increases, delta ferrite will increase, and the formation of intermetallic compound σ phase will also accelerate and increase, thus affecting the performance of the steel. In order to maintain the single austenite structure of austenitic stainless steel, as the silicon content increases, the content of nickel and nitrogen should also increase accordingly. Silicon, as a common deoxidizing element in steel, synergizes with elements such as Cu, Cr, Zr, and Mg to improve the corrosion resistance of steel. Therefore, the mass content of Si in the above is 0.19-0.49%.
[0054] Mn: Manganese has become an important alloying element, and its main function is to form stable austenite with nitrogen and a certain amount of nickel. The strength of chromium-nickel austenitic stainless steel increases with the increase of manganese content. Manganese can improve the thermoplasticity of chromium-nickel austenitic stainless steel, and a significant effect is achieved when the manganese content is 1.5%. Manganese has a strong affinity with sulfur, forming MnS, which is beneficial to eliminate the harmful effects of residual sulfur in steel, but the formation of MnS often leads to a decrease in the resistance of chromium-nickel austenitic stainless steel to chloride pitting corrosion and crevice corrosion. When the sulfur in the steel is reduced to a certain level, the adverse effects of manganese can be basically eliminated, so the mass content of Mn in the above is 7.1-7.4%.
[0055] S: The function is the same as described above.
[0056] P: Function is the same as described above.
[0057] Ni: The main role of nickel in austenitic stainless steel is to form and stabilize austenite to obtain a complete austenitic structure, so that the steel has a good combination of strength, plasticity, toughness and a series of excellent process properties. Within the nickel content range where martensitic transformation can occur in steel, as the nickel content increases, the strength of the steel decreases and the plasticity increases due to the decrease in the amount of martensite. For chromium-manganese-nitrogen austenitic stainless steel with a stable austenitic structure, the addition of nickel can further improve its low-temperature toughness. Nickel can significantly reduce the cold work hardening tendency of austenitic stainless steel, which is mainly because nickel increases the stability of austenite, reduces or even eliminates the martensitic transformation during cold working, while nickel has no obvious cold work hardening effect on austenite itself. Nickel improves the passivation tendency and thermodynamic stability of austenitic stainless steel, thereby improving the alloy's resistance to uniform corrosion and resistance to oxidizing media; as the nickel content increases, the resistance to reducing media is further improved. In austenitic stainless steel, nickel is an important element to improve its resistance to transgranular stress corrosion in some media. The increase in nickel content can reduce the solubility of carbon in austenitic steel, enhance the precipitation tendency of carbides, and reduce the critical carbon content for intergranular corrosion, that is, the sensitivity to intergranular corrosion increases. Therefore, the mass content of Ni in the above-mentioned steel is 1.1-1.9%.
[0058] Cr: Chromium is the main alloying element in austenitic stainless steel. Cr oxide can form a dense passivation film to prevent the oxidation of internal materials. On the other hand, the presence of chromium also increases the electrode potential of Fe, which can effectively prevent the corrosion of Cl- and effectively inhibit Fe 3+ Fe 2+The transformation of chromium into a stable oxide layer makes the microalloyed stainless steel corrosion resistant. In austenitic stainless steel, chromium can increase the solubility of carbon and reduce the depletion of chromium. As the chromium content increases, the tendency of σ phase formation increases. When molybdenum is contained in the steel, the increase in chromium content will also promote the formation of χ phase. Therefore, the mass content of Cr in the above-mentioned steel is 17.1-17.9%.
[0059] Cu: The role of copper in austenitic stainless steel is to significantly reduce its cold work hardening tendency and improve its cold working formability. The combination of copper and molybdenum can further improve the corrosion resistance of austenitic stainless steel in reducing media. The reason why the increase of solid solution copper causes the strength of steel to decrease and the plasticity to increase is that copper can significantly increase the stacking fault energy of chromium-nickel austenitic stainless steel and stabilize the austenite structure. The increase in stacking fault energy hinders the formation of partial dislocations, is conducive to the cross slip of dislocations, prevents the accumulation of dislocations, and improves the plasticity of the material. Copper significantly reduces the hot workability of steel, which is more obvious when the nickel content in austenitic stainless steel is low. Therefore, when the copper content in the steel is high, the nickel content should also be increased accordingly. Copper can significantly improve the corrosion resistance of austenitic stainless steel to reducing media such as sulfuric acid and phosphoric acid. When copper and molybdenum are composite alloyed, the effect is more prominent. The addition of copper accelerates the dissolution of molybdenum in micro-alloyed stainless steel to form MoO4 2- , which strongly promotes the passivation of chromium in microalloyed stainless steel and the enrichment of chromium in the surface film, resulting in improved corrosion resistance of the steel. Therefore, the mass content of Cu in the present invention is 0.49-0.99%.
[0060] N: Nitrogen can significantly improve the strength of austenitic stainless steel through solid solution strengthening without significantly damaging its plasticity and toughness. At the same time, nitrogen can also improve the steel's resistance to uniform corrosion, pitting corrosion, crevice corrosion and intergranular corrosion. This is because nitrogen, as an active element, preferentially gathers along the grain boundaries, reducing the diffusion capacity of carbon atoms and chromium atoms, thereby inhibiting the precipitation of carbides and delaying the formation of σ phase and χ phase. The ability of nitrogen to form austenite is equivalent to that of carbon, about 30 times that of nickel. In austenitic stainless steel, it can replace part of nickel, reduce the ferrite content in steel, and make austenite more stable, and even avoid martensitic transformation. Therefore, the mass content of N in the above is 0.26-0.34%.
[0061] Zr: Its function is the same as that described above, so the mass content of Zr and Mg in the above is 90×10 -4 %≤Zr+Mg≤130×10 -4 %, and the content of Zr and Mg satisfies Zr / Mg=3-6.
[0062] Mg: Its function is the same as described above, so the mass content of Zr and Mg in the above is 90×10 -4 %≤Zr+Mg≤130×10 -4%, and the content of Zr and Mg satisfies Zr / Mg=3-6.
[0063] Furthermore, the micro-alloyed stainless steel is prepared by the following steps: taking the following raw materials according to weight ratio: 30-50% of ultra-low P industrial pure iron, 10-20% of high carbon ferrochrome, and 40-60% of molten iron smelted from laterite nickel ore; firstly adding the ultra-low P industrial pure iron and the high carbon ferrochrome into a vacuum induction furnace for smelting, then adding the molten iron smelted from laterite nickel ore into the vacuum induction furnace, and then casting into a steel billet of the micro-alloyed stainless steel by a die casting process, and finally forging or hot rolling the steel billet of the micro-alloyed stainless steel to obtain it.
[0064] The beneficial effect of the present invention adopting the above further technical solution is: using the molten iron rich in chromium and nickel smelted from laterite nickel ore as the raw material for smelting micro-alloyed stainless steel, the precious metal elements Cr and Ni are saved. Using industrial pure iron can reduce impurities such as P and S, which is not only conducive to reducing the harmful impurity P in micro-alloyed stainless steel, but also reduces the content of other impurities. The Cr and C required for micro-alloyed stainless steel can be matched by ferrochrome, and C can release heat by oxidation during smelting, which plays a role in raising the temperature and is conducive to the smelting process. Micro-alloyed stainless steel has strong organizational stability, good high-temperature thermoplasticity and high-temperature oxidation resistance, and more excellent local corrosion properties such as seawater resistance and comprehensive mechanical properties.
[0065] The ultra-low P industrial pure iron mentioned above has P≤0.0035wt%, C≤0.005wt%; the high carbon ferrochrome has Cr≥60wt%, C≤6.5wt%; the molten iron smelted from laterite nickel ore has Cr≥60wt%, P≤0.01wt%.
[0066] Furthermore, the covering agent includes the following chemical components by mass percentage: CaF2 55-59%, CaO13-19%, MgO 5-9%, Al2O3 5-12%, SiO2 6-9% five-element slag system. The slag system is pre-melted at 1300-1400°C for 4-6 hours. The pre-melted slag covering agent is used after being baked at 400-600°C for 6-8 hours.
[0067] A second aspect of the present invention provides a stainless steel easy-to-weld high-strength steel composite billet, wherein the microalloyed stainless steel easy-to-weld high-strength steel composite billet is prepared by any of the preparation methods described above.
[0068] The third aspect of the present invention provides a microalloyed stainless steel easily welded high-strength steel composite material, which is obtained by heating and rolling the microalloyed stainless steel easily welded high-strength steel composite billet as described above.
[0069] Furthermore, the microalloyed stainless steel easy-to-weld high-strength steel composite material is a composite steel plate material with a thickness of 6-80 mm.
[0070] The specific process of the above heating and rolling includes: placing the microalloyed stainless steel easy-to-weld high-strength steel composite billet in a high-purity nitrogen or pure hydrogen protective atmosphere, the soaking temperature is 1150-1250°C, the holding time is 2-4 hours, the start rolling temperature is 1100-1200°C, the first pass reduction is 15-35%, the cumulative reduction is 70-95%, the first rolling time is controlled to be 1-2 hours, and the second rolling time is controlled to be 2-2.5 hours. During the hot rolling process, the first two passes are unidirectional rolling, that is, after the first pass is completed, the roll gap remains unchanged, and the rolled piece is returned to the original rolling mill entrance by the rolling roller, and then pressed down and rolled. After two cycles, the remaining rolling passes are reciprocating reversible rolling; during the rolling process, when the temperature of the composite slab is lower than 900°C, it is heated online to 920-1020°C by induction heating, and then the hot rolling process is continued until the finished product thickness reaches 6-80mm, obtaining a micro-alloyed stainless steel, easy-to-weld, high-strength steel composite steel plate material.
[0071] The present invention adopts micro-alloyed stainless steel easy-to-weld high-strength steel composite blank to manufacture bimetallic composite steel plate material, that is, micro-alloyed stainless steel easy-to-weld high-strength steel composite steel plate material, the interface bonding strength of functionalized metal and structural metal can reach 220-600MPa and above, and has excellent corrosion resistance, heat resistance and other special properties. It can be widely used in marine engineering, ships, petroleum, chemical industry, nuclear power, bridges, construction, urban pipelines, industrial pipelines, underground facilities and other fields, and has huge domestic market demand; it can partially replace expensive micro-alloyed stainless steel and reduce the cost of use; at the same time, it is also conducive to replacing high-end composite steel plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 The optical microstructure photographs of the composite billet after rolling of the present invention, wherein (a) is an optical microstructure photograph of the structure of the easy-to-weld high-strength steel at 200 μm, (b) is an optical microstructure photograph of the structure of the easy-to-weld high-strength steel at 100 μm, (c) is an optical microstructure photograph of the composite boundary area at 200 μm after the composite billet is rolled, and (d) is an optical microstructure photograph of the composite boundary area at 100 μm after the composite billet is rolled;
[0073] Figure 2 The composite billet of the present invention is a scanning electron microscope photograph after rolling, wherein (a) is a scanning electron microscope photograph of the structure of the easy-to-weld high-strength steel at 100 μm, (b) is a scanning electron microscope photograph of the structure of the easy-to-weld high-strength steel at 10 μm, (c) is a scanning electron microscope photograph I of the composite boundary area at 100 μm after the composite billet is rolled, and (d) is a scanning electron microscope photograph II of the composite boundary area at 100 μm after the composite billet is rolled;
[0074] Figure 3 The scanning electron microscope photographs of the composite billet of the present invention after rolling under cupric chloride corrosion, wherein (a) is a scanning electron microscope photograph of the easy-to-weld high-strength steel at 4 μm, (b) is a scanning electron microscope photograph of the microalloyed stainless steel at 4 μm, (c) is a scanning electron microscope photograph of the composite boundary area at 20 μm after the composite billet is rolled, and (d) is a scanning electron microscope photograph of the composite boundary area at 5 μm after the composite billet is rolled;
[0075] Figure 4 EBSD diagrams of the microalloyed stainless steel and the easily welded high-strength steel of the present invention; wherein (a) is the IQ diagram of the microalloyed stainless steel, (b) is the IQ diagram of the easily welded high-strength steel, (c) is the Euler diagram of the microalloyed stainless steel, and (d) is the Euler diagram of the easily welded high-strength steel;
[0076] Figure 5 The IPF diagram of the microalloyed stainless steel and the easily welded high-strength steel of the present invention, wherein (a) is the microalloyed stainless steel; (b) is the easily welded high-strength steel;
[0077] Figure 6 EBSD images of the composite boundary area after rolling of the composite billet of the present invention, wherein (a) is a microstructure image of the composite boundary area, (b) is a grain orientation image of the composite boundary area, and (c) is a grain orientation image of the composite boundary area;
[0078] Figure 7 The composite boundary area line scan diagram of the composite billet after rolling of the present invention, wherein (a) is the line scan position diagram, (b) is the element distribution diagram, and (c) is the enlarged element distribution diagram;
[0079] Figure 8 The surface scan diagram of the composite boundary area after rolling of the composite billet of the present invention, wherein (a) is the surface distribution diagram of the C element, (b) is the surface distribution diagram of the Si element, (c) is the surface distribution diagram of the Mn element; and (d) is the surface distribution diagram of the Cr element. DETAILED DESCRIPTION
[0080] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0081] Example 1: Martensitic stainless steel easy-to-weld high-strength steel composite billet
[0082] The present embodiment relates to a method for preparing a martensitic stainless steel easy-to-weld high-strength steel composite billet, comprising the following steps: using easy-to-weld high-strength steel as a master batch, using micro-alloyed low-cost martensitic stainless steel as a consumable electrode, and using alkaline slag as a covering agent to perform electroslag welding, wherein the voltage of the electroslag welding is 30-45V, the current is 1000-2000A, and the time is 0.5-3.5 hours. After welding, water cooling or air cooling is performed to form a micro-alloyed martensitic stainless steel easy-to-weld high-strength steel composite billet.
[0083] Preferably, the easy-to-weld high-strength steel comprises the following chemical components by mass percentage: C: 0.009-0.049%, Si: 0.011-0.049%, Mn: 0.51-1.49%, 90×10 -4 %≤Mg+Zr≤130×10 -4 %, and the contents of Mg and Zr satisfy the following formula: Zr / Mg=3-6, and the balance is Fe.
[0084] Preferably, the easy-to-weld high-strength steel is prepared by the following steps: the chemical components of the easy-to-weld high-strength steel are first smelted in a vacuum induction furnace, then cast into a steel billet by a die casting process, and finally the steel billet is forged or hot rolled.
[0085] Preferably, the microalloyed low-cost martensitic stainless steel comprises the following chemical components by mass percentage: 0.26wt% C, 0.19wt% Si, 0.19wt% Mn, 0.0010wt% S, 0.010wt% P, 1.1wt% Ni, 12.1wt% Cr, 0.0040wt% Zr, 0.0010wt% Mg, 0.0050wt% Ti, and the balance is Fe.
[0086] Preferably, the micro-alloyed low-cost martensitic stainless steel is prepared by the following steps: the ingredients are prepared in the following manner: ultra-low P industrial pure iron is used as the smelting base material, accounting for 30% by mass; high carbon ferrochrome is added, accounting for 20% by mass; and then molten iron smelted using laterite nickel ore is added, accounting for 50% by mass. Among them, P≤0.0035wt% and C≤0.005wt% in ultra-low P industrial pure iron. Cr≥60wt% and C≤6.5wt% in high carbon ferrochrome. Cr≥60wt% and P≤0.01wt% of the molten iron smelted from laterite nickel ore. Ultra-low P industrial pure iron and high carbon ferrochrome are melted in a medium frequency furnace, and then molten iron smelted using laterite nickel ore is added to obtain a low-phosphorus raw material for smelting micro-alloyed low-cost martensitic stainless steel. After smelting, P≤0.014wt% in the micro-alloyed low-cost martensitic stainless steel;
[0087] Specifically, the refining, continuous casting, rolling and solution treatment in the smelting of the above-mentioned microalloyed low-cost martensitic stainless steel are carried out according to the following steps:
[0088] ①LF refining outside the furnace: slag flow and slag removal before tapping, try to clean the slag as much as possible; white slag tapping, a small amount of lime and fluorite can be used to adjust the slag reducibility and fluidity; tapping temperature is 1530℃; first turn on the power to melt the top slag, then perform alloy fine-tuning and micro-alloying to obtain the various components of the above-mentioned micro-alloyed low-cost martensitic stainless steel; the smelting time of the LF refining furnace is 45min.
[0089] ②Continuous casting: tundish temperature 1465℃; working casting speed 1.05m / min; water volume on the wide surface of the crystallizer is 175m 3 / h, narrow surface water volume is 20m 3 / h, the inlet and outlet water temperature difference is 5℃; the crystallizer adopts non-sinusoidal vibration, the frequency is 140CPM, and the amplitude is 3.0mm; the crystallizer protective slag is high nitrogen protective slag.
[0090] ③ Rolling: The continuous casting billet is first heated and then hot-rolled to obtain a hot-rolled black coil; the hot rolling temperature is 1150°C.
[0091] ④ Heat treatment: Heat to 950℃ and keep warm for 60min for water quenching, then temper at 450℃ and cool to room temperature in air.
[0092] Example 2: Ferritic stainless steel easy-to-weld high-strength steel composite billet
[0093] The present embodiment relates to a preparation method of a ferritic stainless steel easy-to-weld high-strength steel composite billet, comprising the following steps: using easy-to-weld high-strength steel as a master batch, using micro-alloyed low-cost ferritic stainless steel as a consumable electrode, and using alkaline slag as a covering agent to perform electroslag welding, wherein the voltage of the electroslag welding is 30-45V, the current is 1000-2000A, and the time is 0.5-3.5 hours. After welding, water cooling or air cooling is performed to form a ferritic stainless steel easy-to-weld high-strength steel composite billet.
[0094] Preferably, the chemical composition and content of the easy-to-weld high-strength steel are: C: 0.009-0.049%, Si: 0.011-0.049%, Mn: 0.51-1.49%, 90×10 -4 %≤Mg+Zr≤130×10 -4 %, and the contents of Mg and Zr satisfy the following formula: Zr / Mg=3-6, the balance is Fe
[0095] Preferably, the easy-to-weld high-strength steel is prepared by the following steps: the chemical components of the easy-to-weld high-strength steel are first smelted in a vacuum induction furnace, then cast into a steel billet by a die casting process, and finally the steel billet is forged or hot rolled.
[0096] Preferably, the microalloyed low-cost ferritic stainless steel comprises the following chemical components by mass percentage: 0.009wt% C, 0.29wt% Si, 0.0014wt% S, 0.009wt% P, 1.5wt% Ni, 19.5wt% Cr, 0.29wt% Cu, 0.007wt% N, 0.0050wt% Mg, 0.0200wt% Zr, and the balance is Fe.
[0097] Preferably, the microalloyed low-cost ferritic stainless steel is prepared by the following steps: the ingredients are prepared in the following manner: ultra-low P industrial pure iron is used as the smelting base material, accounting for 34% by mass; high carbon ferrochrome is added, accounting for 14% by mass; and then molten iron smelted using laterite nickel ore is added, accounting for 52% by mass. Among them, P≤0.0050wt% and C≤0.01wt% in industrial pure iron. Cr≥60wt% and C≤9.5wt% in high carbon ferrochrome. Cr≥60wt% and P≤0.03wt% of the molten iron smelted from laterite nickel ore are used. Ultra-low P industrial pure iron and high carbon ferrochrome are melted in a medium frequency furnace, and then molten iron smelted using laterite nickel ore is added to obtain a low-phosphorus raw material for smelting microalloyed low-cost ferritic stainless steel. After smelting, P≤0.015wt% in the microalloyed low-cost ferritic stainless steel is obtained.
[0098] Specifically, the refining, continuous casting, rolling and solution treatment in the smelting of the above-mentioned micro-alloyed low-cost ferritic stainless steel are carried out according to the following steps:
[0099] ① LF refining outside the furnace: slag flow and slag removal before tapping, try to clean the slag; white slag tapping, a small amount of lime and fluorite can be used to adjust the slag reducibility and fluidity; tapping temperature is 1630°C; firstly, power is turned on to melt the top slag, and then alloy fine-tuning and micro-alloying are performed to obtain a chemical composition by weight percentage including: 0.10wt% C, 0.25wt% Si, 7.2wt% Mn, 0.0011wt% S, 0.011wt% P, 1.4wt% Ni, 7.5wt% Cr, 0.59wt% Cu, 0.30wt% N, 0.0025wt% Mg, 0.0080wt% Zr, and the balance is Fe; the smelting time of the LF refining furnace is 60min.
[0100] ②Continuous casting: tundish temperature 1470℃; working speed 1.10m / min; water volume on the wide surface of the crystallizer is 185m 3 / h, narrow surface water volume is 24m 3 / h, the inlet and outlet water temperature difference is 6°C; the crystallizer adopts non-sinusoidal vibration, the frequency is 140CPM, and the amplitude is 3.0mm; the crystallizer protective slag is high nitrogen protective slag.
[0101] ③ Rolling: The continuous casting billet is first heated and then hot-rolled to obtain a hot-rolled black coil; the hot rolling temperature is 1200°C.
[0102] ④Heat treatment: heating at 800℃, keeping warm, then air cooling or furnace cooling.
[0103] Example 3: Austenitic stainless steel easy-to-weld high-strength steel composite billet
[0104] The present embodiment relates to a method for preparing an austenitic stainless steel easy-to-weld high-strength steel composite billet, comprising the following steps: using easy-to-weld high-strength steel as a master batch, using micro-alloyed nickel-saving austenitic stainless steel as a consumable electrode, and using alkaline slag as a covering agent to perform electroslag welding, wherein the voltage of the electroslag welding is 30-45V, the current is 1000-2000A, and the time is 0.5-3.5 hours. After welding, water cooling or air cooling is performed to form an austenitic stainless steel easy-to-weld high-strength steel composite billet.
[0105] Preferably, the easy-to-weld high-strength steel comprises the following chemical components by mass percentage: C: 0.009-0.049%, Si: 0.011-0.049%, Mn: 0.51-1.49%, 90×10 -4 %≤Mg+Zr≤130×10 -4 %, and the contents of Mg and Zr satisfy the following formula: Zr / Mg=3-6, and the balance is Fe.
[0106] Preferably, the easy-to-weld high-strength steel is prepared by the following steps: the chemical components of the easy-to-weld high-strength steel are first smelted in a vacuum induction furnace, then cast into a steel billet by a die casting process, and finally the steel billet is forged or hot rolled.
[0107] Preferably, the microalloyed nickel-saving austenitic stainless steel comprises the following chemical components in mass percentage: 0.12wt% C, 0.49wt% Si, 7.3wt% Mn, 0.0010wt% S, 0.012wt% P, 1.8wt% Ni, 17.5wt% Cr, 0.89wt% Cu, 0.30wt% N, 0.0020wt% Mg, 0.0090wt% Zr, and the balance is Fe.
[0108] Preferably, the microalloyed nickel-saving austenitic stainless steel is prepared by the following steps: the ingredients are prepared in the following manner: ultra-low P industrial pure iron is used as the smelting base material, accounting for 35% by mass; high carbon ferrochrome is added, accounting for 15% by mass; and then molten iron smelted using laterite nickel ore is added, accounting for 60% by mass. Among them, P≤0.0050wt% and C≤0.01wt% in industrial pure iron. Cr≥60wt% and C≤9.5wt% in high carbon ferrochrome. Cr≥60wt% and P≤0.03wt% of the molten iron smelted from laterite nickel ore are used. Ultra-low P industrial pure iron and high carbon ferrochrome are melted in a medium frequency furnace, and then molten iron smelted using laterite nickel ore is added to obtain a low-phosphorus raw material for smelting microalloyed nickel-saving microalloyed stainless steel. After smelting, P≤0.012wt% of the microalloyed nickel-saving microalloyed stainless steel is obtained.
[0109] Specifically, the refining, continuous casting, rolling and solution treatment in the smelting of the microalloyed nickel-saving austenitic stainless steel are carried out according to the following steps:
[0110] ①LF refining outside the furnace: slag flow and slag removal before tapping, try to clean the slag; white slag tapping, a small amount of lime and fluorite can be used to adjust the slag reducibility and fluidity; tapping temperature is 1730℃; firstly, power on to melt the top slag, and then perform alloy fine-tuning and micro-alloying to obtain the chemical composition by weight percentage: 0.20wt% C, 0.49wt% Si, 7.6wt% Mn, 0.0020wt% S, 0.020wt% P, 1.8wt% Ni, 18.5wt% Cr, 0.89wt% Cu, 0.40wt% N, 0.0020wt% Mg, 0.0090wt% Zr, and the balance is Fe; the smelting time of the LF refining furnace is 90min. The smelting time of the LF refining furnace is 90min.
[0111] ②Continuous casting: tundish temperature 1480℃; working speed 1.20m / min; water volume on the wide surface of the crystallizer is 195m 3 / h, narrow surface water volume is 25m 3 / h, the inlet and outlet water temperature difference is 7℃; the crystallizer adopts non-sinusoidal vibration, the frequency is 140CPM, and the amplitude is 3.0mm; the crystallizer protective slag is high nitrogen protective slag.
[0112] ③ Rolling: The continuous casting billet is first heated and then hot-rolled to obtain a hot-rolled black coil; the hot rolling temperature is 1250°C.
[0113] ④ Solution treatment: Solution treatment is carried out after hot rolling. The solution treatment temperature is 1150°C, the solution time is 1.0 mm / min, the air cooling + water cooling time is 120 min, and after air cooling, room temperature water cooling is carried out to obtain micro-alloyed nickel-saving austenitic stainless steel.
[0114] Example 4: Microalloyed stainless steel and easy-to-weld high-strength steel composite steel plate material
[0115] The microalloyed stainless steel easy-to-weld high-strength steel composite billet described in any one of the above embodiments 1 to 3 is heated and rolled to obtain a microalloyed stainless steel easy-to-weld high-strength steel composite steel plate material.
[0116] The specific process of the above heating and rolling includes: placing the microalloyed stainless steel easy-to-weld high-strength steel composite billet in a high-purity nitrogen or pure hydrogen protective atmosphere, the soaking temperature is 1150-1250°C, the holding time is 2-4 hours, the start rolling temperature is 1100-1200°C, the first pass reduction is 15-35%, the cumulative reduction is 70-95%, the first rolling time is controlled to be 1-2 hours, and the second rolling time is controlled to be 2-2.5 hours. During the hot rolling process, the first two passes are unidirectional rolling, that is, after the first pass is completed, the roll gap remains unchanged, and the rolled piece is returned to the original rolling mill entrance by the rolling roller, and then pressed down and rolled. After two cycles, the remaining rolling passes are reciprocating reversible rolling; during the rolling process, when the temperature of the composite slab is lower than 900°C, it is heated online to 920-1020°C by induction heating, and then the hot rolling process is continued until the finished product thickness reaches 10-60mm, obtaining a micro-alloyed stainless steel, easy-to-weld, high-strength steel composite steel plate material.
[0117] Test example: Study on the interface and microstructure of bimetallic composites
[0118] The test sample is a microalloyed stainless steel easy-to-weld high-strength steel composite steel plate material prepared in Example 1 by hot rolling the martensitic stainless steel easy-to-weld high-strength steel composite billet through Example 4. The thickness of the composite steel plate material is 30 mm.
[0119] (1) Optical microscopy characterization
[0120] The samples were prepared for metallographic analysis using 4% HNO3 as the etchant, and the microstructure was observed and analyzed using an optical microscope. Figure 1 The optical microstructure photos of the composite billet after rolling of the present invention, (a) and (b) are the structures of the easily welded high-strength steel, which are ferrite + pearlite, while the microalloyed stainless steel has almost no obvious corrosion, and the boundary between the easily welded high-strength steel and the microalloyed stainless steel is obvious (see Figure 1 (c), (d)), the composite interface is clear and intact, and no obvious holes or poorly composited areas are found, indicating that the mutual diffusion of heterogeneous atoms makes the composite interface produced by electroslag welding a metallurgical bond, achieving atomic bonding and greatly improving the bonding quality of the composite plate interface.
[0121] (2) Scanning electron microscopy characterization
[0122] Figure 2 The scanning electron microscope pictures of the composite billet of the present invention after rolling are shown in (a) and (b). The microalloyed stainless steel has almost no obvious corrosion in the corrosive agent of nitric acid alcohol. The boundary between the microalloyed stainless steel and the microalloyed stainless steel can be seen more clearly from the scanning electron microscope pictures (see Figure 2(c), (d)), and it can be seen that there is a transition layer between the easy-to-weld high-strength steel and the micro-alloyed stainless steel, and the thickness of the transition layer is 2-4μm.
[0123] Figure 3 The scanning electron microscope photograph of the composite billet of the present invention after rolling under cupric chloride corrosion. Figure 3 ((a)-(d)) shows that Figure 2 ((a)-(d)) Similar results are also shown. It can be seen that there is a transition layer between the easy-to-weld high-strength steel and the micro-alloyed stainless steel. The thickness of the transition layer is 2-4μm.
[0124] (3) EBSD characterization
[0125] Figure 4 EBSD diagrams of the microalloyed stainless steel and the easily welded high-strength steel of the present invention and Figure 5 is the IPF diagram of the microalloyed stainless steel and the easily welded high-strength steel of the present invention; from IQ( Figure 4 (a) and (b)), Euler diagram ( Figure 4 (c) and (d)), IPF graph ( Figure 5 In (a) and (b), it can be seen that the microalloyed stainless steel is a ferrite + martensite structure with a striped distribution, and the easily welded high-strength steel is a ferrite + pearlite structure. Figure 6 This is the EBSD map of the composite boundary area after the composite billet of the present invention is rolled. Figure 6 In (a)-(c) , it can be seen that the microalloyed stainless steel structure is significantly refined near the dividing line, the band distribution phenomenon no longer appears, and no obvious transition zone appears, while the size of the easy-to-weld high-strength steel structure in the lower part does not change much.
[0126] (4) EPMA characterization
[0127] The composite plate is glued to the laboratory table with conductive tape, and it is necessary to ensure that the conductive tape contacts the metal specimen to be observed. The test bench with the bonded specimen is placed in the EPMA equipment, and then line scanning and surface scanning are performed to analyze the diffusion of elements. The main components of the composite plate are easy-to-weld high-strength steel and micro-alloyed stainless steel. They are corroded with 4% nitric acid alcohol solution until the interface is exposed, and line scanning and surface scanning are performed perpendicular to the interface (such as Figure 7 and 8 ). Figure 7The red line in the middle represents the scanning path. The diffusion of C, Si, Mn and Cr elements in the composite plate is analyzed. It is found that the carbon element is evenly distributed on the easy-to-weld high-strength steel and micro-alloyed stainless steel, but the carbon content of the two has obvious peaks at the interface. The content of Mn and Si elements as the main alloying elements in the easy-to-weld high-strength steel is significantly higher on the easy-to-weld high-strength steel side than on the micro-alloyed stainless steel side, while the content of Cr element on the micro-alloyed stainless steel side is significantly higher than that on the easy-to-weld high-strength steel side, and the elements show a certain slope on the interface. Figure 8 The same results were obtained from the surface scanning, indicating that there is a diffusion layer between the easy-to-weld high-strength steel and the micro-alloyed stainless steel.
[0128] (5) Bimetallic interface bonding strength
[0129] The shear test results of the high-strength steel / microalloyed stainless steel composite plate are 272-291MPa, indicating that the interface has excellent shear strength. The bending test uses a bending angle of 180° and a bending core diameter of 20mm. The positive and reverse bending tests are carried out. The results show that no cracks are found on the outside of the bending part, no delamination is observed at the composite interface, and the bending part is intact.
[0130] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0131] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a stainless steel easy-to-weld high-strength steel composite blank, characterized in that: The method comprises the following steps: using easy-to-weld high-strength steel as a master batch, using microalloyed stainless steel as a consumable electrode, using alkaline slag as a covering agent, performing electroslag welding, wherein the voltage of the electroslag welding is 30-45V, the current is 1000-2000A, the time is 0.5-3.5 hours, and cooling to obtain a microalloyed stainless steel easy-to-weld high-strength steel composite blank; The easy-to-weld high-strength steel includes the following chemical components by mass percentage: C: 0.009-0.049%, Si: 0.011-0.049%, Mn: 0.51-1.49%, 90×10 -4 %≤Mg+Zr≤130×10 -4 %, and the content of Mg and Zr satisfies Zr / Mg=3-6, and the balance is Fe; The microalloyed stainless steel includes microalloyed low-cost ferritic stainless steel or microalloyed nickel-saving austenitic stainless steel; The microalloyed low-cost ferritic stainless steel comprises the following chemical components by mass percentage: C≤0.009%, Si: 0.19-0.49%, S≤0.0014%, P≤0.009%, Ni: 1.1-1.9%, Cr: 19.1-19.9%, Cu: 0.19-0.49%, N≤0.008%, 70×10 -4 %≤Mg+Zr≤290×10 -4 %, and the content of Zr and Mg satisfies Zr / Mg=3-6, and the balance is Fe and unavoidable impurities; The microalloyed nickel-saving austenitic stainless steel comprises the following chemical components by mass percentage: C: 0.09-0.14%, Si: 0.19-0.49%, Mn: 7.1-7.4%, S≤ 0.0014%, P≤ 0.014%, Ni: 1.1-1.9%, Cr: 17.1-17.9%, Cu: 0.49-0.99%, N: 0.26-0.34%, 90×10 -4 %≤Zr+Mg≤130×10 -4 %, and the content of Zr and Mg satisfies Zr / Mg=3-6, and the balance is Fe and unavoidable impurities.
2. The method for preparing a stainless steel easy-to-weld high-strength steel composite blank according to claim 1, characterized in that: The easy-to-weld high-strength steel is prepared by the following steps: firstly melting the chemical components of the easy-to-weld high-strength steel in a vacuum induction furnace, then casting the steel billet in a die casting process, and finally forging or hot rolling the steel billet; Or the easy-to-weld high-strength steel is prepared by the following steps: the chemical components of the easy-to-weld high-strength steel are first smelted in a converter or an electric furnace, then refined in an LF furnace, a VD furnace or an RH furnace, then cast into a steel billet by a continuous casting process, and finally the steel billet is forged or hot-rolled.
3. The method for preparing a stainless steel easy-to-weld high-strength steel composite blank according to claim 2, characterized in that: The micro-alloyed stainless steel is prepared by the following steps: taking the following raw materials according to weight ratio: 30-50% ultra-low P industrial pure iron, 10-20% high carbon ferrochrome, and 40-60% molten iron smelted from laterite nickel ore; firstly adding the ultra-low P industrial pure iron and the high carbon ferrochrome into a vacuum induction furnace for smelting, then adding the molten iron smelted from laterite nickel ore into the vacuum induction furnace, and then casting into a steel billet of the micro-alloyed stainless steel by a die casting process, and finally forging or hot rolling the steel billet of the micro-alloyed stainless steel to obtain the obtained steel billet.
4. The method for preparing a stainless steel easy-to-weld high-strength steel composite blank according to claim 1, characterized in that: The covering agent comprises the following chemical components in terms of mass percentage: CaF2 55-59%, CaO 13-19%, MgO 5-9%, Al2O3 5-12%, and SiO2 6-9%.
5. A stainless steel easy-to-weld high-strength steel composite blank, characterized in that: The microalloyed stainless steel easy-to-weld high-strength steel composite billet is prepared by the preparation method according to any one of claims 1 to 4.
6. A microalloyed stainless steel easily welded high-strength steel composite material, characterized in that: The microalloyed stainless steel easy-to-weld high-strength steel composite blank as claimed in claim 5 is heated and rolled to obtain a microalloyed stainless steel easy-to-weld high-strength steel composite material.
7. The microalloyed stainless steel easy-to-weld high-strength steel composite material according to claim 6, characterized in that: The microalloyed stainless steel easy-to-weld high-strength steel composite material is a composite steel plate material, and the thickness of the composite steel plate material is 6-80 mm.
Citation Information
Patent Citations
Method for preparing bimetal composite plate through electroslag casting
CN113523246A
Microalloy low-cost martensitic stainless steel and manufacturing method thereof
CN116356208A